Highlights from Faraday Discussion 300: hot electron science and microscopic processes in plasmonics and catalysis, London, UK, February 2019. Issue 50 (6th June 2019) - Zaleska, Anastasia; Glass, Daniel
Abstract : The 300th Faraday discussion on hot electron processes in plasmonics and catalysis brought together a wide spectrum of delegates from across the globe. In this paper we present a brief overview of the themes and topics presented at this meeting, highlighting the major findings of each presentation. Abstract : The 300th Faraday discussion on hot electron processes in plasmonics and catalysis brought together a wide spectrum of delegates from across the globe. Scientists from across multiple disciplines, with a broad spectrum of experience and expertise, joined together in hope of identifying and answering the latest problems within the ever growing hot electron science community. In this paper we present a brief overview of the themes and topics presented at this meeting, highlighting the major findings of each presentation.